О сингуларисном разложении скачкообразной функции - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
A singular expansion for the jump-like function is given. This expansion includes an exponentially increasing function and the exponentially decreasing sum of harmonic functions.